2013
DOI: 10.1590/s0100-736x2013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento, caracterização e diferenciação de células-tronco mesenquimais do líquido amniótico equino obtido em diferentes idades gestacionais

Abstract: O interesse nas pesquisas com células-tronco derivadas de anexos fetais de diversas espécies cresceu exponencialmente nas últimas décadas em virtude de serem fontes de células-tronco adultas com potencial de diferenciação em diversas linhagens celulares que apresentam pouca ou nenhuma imunogenicidade, apresentando-se assim como alternativa de grande importância para a formação de bancos celulares. Apesar do crescente interesse, os estudos para espécie equina ainda são escassos. O objetivo deste trabalho foi is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
1
6
0
3
Order By: Relevance
“…al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 86%
“…De Vita et al (2013), studying mesenchymal stem cells from equine amniotic fluid, reported an initial difficulty in cell isolation, and achieved better cell adhesion on the culture plate by decreasing the amount of medium in the primary culture to leave the cells closest to the plate, and by increasing the time to the first exchange of medium from 2 to 7 days, to prevent the removal of cells that were capable of adhesion and were still in suspension. Vidal et al (2007) also observed that cell populations obtained from adipose tissue did not form as many colonies as cells from bone marrow, and that they were distributed more uniformly and adhered more firmly to the culture plate, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study [50] with amniotic fluid demonstrated that the CD90 marker decreases as pregnancy develops. This inverse relationship may explain the findings in this present study because the samples collected in the slaughterhouse were from the final months of gestation (9 to 10 months).…”
Section: Discussionmentioning
confidence: 99%
“…As células obtidas também podem ser utilizadas na forma cultivada ou não cultivada, isto é, quando o tratamento é feito com a fração mononuclear e com a fração vascular estromal logo após a aspiração (MAIA et al, 2013).…”
Section: Scutt; Stolzing 2006)unclassified